Prevalence rate of Salmonella in Babylon province - AL-Taie, Hydar Hamza Ibraheem (The Iraqi Journal of Veterinary Medicine, 2009)
Three handed stool samples of an a apparently normal adults individualscomprising hospital personnel , buffalo owners and employers processing chicken werecollected and examined during period from January 2008 to January 2009 toinvestigate the presences of Salmonella in Babylon province. Out of the total 300samples examined by stool cultures on different media confirmed by biochemical testsand the isolated was serotypes on central lab. Result showed that 17 samples gavepositive results for salmonella which comprise 5.66% of total percentage and Buffaloowners revealed the highest carrier rate 8 %